Soft Interactions with Model Crowders and Non-canonical Interactions with Cellular Proteins Stabilize RNA Folding. Issue 4 (16th February 2018) - Daher, May; Widom, Julia R.; Tay, Wendy; Walter, Nils G.
Abstract: Living cells contain diverse biopolymers, creating a heterogeneous crowding environment, the impact of which on RNA folding is poorly understood. Here, we have used single-molecule fluorescence resonance energy transfer to monitor tertiary structure formation of the hairpin ribozyme as a model to probe the effects of polyethylene glycol and yeast cell extract as crowding agents. As expected, polyethylene glycol stabilizes the docked, catalytically active state of the ribozyme, in part through excluded volume effects; unexpectedly, we found evidence that it additionally displays soft, non-specific interactions with the ribozyme. Yeast extract has a profound effect on folding at protein concentrations 1000-fold lower than found intracellularly, suggesting the dominance of specific interactions over volume exclusion. Gel shift assays and affinity pull-down followed by mass spectrometry identified numerous non-canonical RNA-binding proteins that stabilize ribozyme folding; the apparent chaperoning activity of these ubiquitous proteins significantly compensates for the low-counterion environment of the cell. Graphical Abstract: Highlights: smFRET of the hairpin ribozyme quantifies effects of PEG and yeast cell extract as crowding agents. PEG stabilizes the docking compaction of the catalytically active ribozyme, in part through EV effects. PEG additionally displays soft, non-specific interactions with the RNA. Yeast cell extract contains multiple proteins that exhibit non-canonical binding to RNA Metabolic enzymes act as ubiquitous RNA chaperones, compensating for the low-counterion environment of the cell.